Mineral changes in cement-sandstone matrices induced by biocementation. (June 2016) - Verba, C.; Thurber, A.R.; Alleau, Y.; Koley, D.; Colwell, F.; Torres, M.E.
Graphical abstract: Highlights: Sporosarcina pasteurii is a bacterium that has demonstrated the potential ability to seal to a compromised wellbore through the enzymatic precipitation of CaCO3 . Sporosarcina pasteurii can survive in Illinois basin formation fluid under high pressure CO2 and temperature conditions. At 30 °C under 10 MPa PCO2, S. pasteurii promoted additional CaCO3 precipitation compared to abiotic samples. Abstract: Prevention of wellbore CO2 leakage is a critical component of any successful carbon capture, utilization, and storage program. Sporosarcina pasteurii is a bacterium that has demonstrated the potential ability to seal a compromised wellbore through the enzymatic precipitation of CaCO3 . Here we investigate the growth of S. pasteurii in a synthetic brine that mimics the Illinois Basin and on Mt. Simon sandstone encased in Class H Portland cement under high pressure and supercritical CO2 (PCO2 ) conditions. The bacterium grew optimum at 30 °C compared to 40 °C under ambient and high pressure (10 MPa) conditions; and growth was comparable in experiments at high PCO2 . Sporosarcina pasteurii actively induced the biomineralization of CaCO3 polymorphs and MgCa(CO3 )2 in both ambient and high pressure conditions as observed in electron microscopy. In contrast, abiotic (non-biological) samples exposed to CO2 resulted in the formation of surficial vaterite and calcite. The ability of S. pasteurii to grow under subsurface conditions may be a promising mechanism to enhance wellbore integrity.